Development and psychometric evaluation of a formative assessment instrument for higher order thinking skills in Akidah Akhlak Phase E - Chamelia Nurani; Rizki Rahmawati (Eduvista: Journal of Education and Innovation, 2026)
Formative assessment plays an essential role in fostering Higher Order Thinking Skills (HOTS); however, the development of HOTS assessment instruments for Akidah Akhlak supported by comprehensive psychometric evaluation remains limited. This study aimed to develop a formative HOTS assessment instrument for Akidah Akhlak Phase E and evaluate its psychometric quality. An instrument development study was employed through construct analysis, instrument development, content validation by two experts, field testing involving 35 students, and psychometric evaluation using Aiken's V, Product Moment correlation, Cronbach's Alpha, and ITEMAN. The findings revealed a mean Aiken's V of 0.846, 34 of 35 items (97.14%) met the empirical validity criteria, a reliability coefficient of 0.929, and item characteristics were dominated by moderate difficulty, very good discrimination, and fully functioning distractors. This study contributes a valid and reliable HOTS assessment instrument and a psychometric-based instrument development framework to support evidence-based formative assessment in Akidah Akhlak learning. Abstrak Asesmen formatif berperan penting dalam mengembangkan Higher Order Thinking Skills (HOTS), namun pengembangan instrumen pada mata pelajaran Akidah Akhlak yang disertai evaluasi psikometrik secara komprehensif masih terbatas. Penelitian ini bertujuan mengembangkan instrumen asesmen formatif HOTS pada mata pelajaran Akidah Akhlak Fase E serta mengevaluasi kualitas psikometriknya. Penelitian menggunakan pendekatan instrument development study melalui analisis konstruk, pengembangan instrumen, validasi isi oleh dua ahli, uji coba kepada 35 peserta didik, serta evaluasi psikometrik menggunakan Aiken's V, korelasi Product Moment, Cronbach's Alpha, dan ITEMAN. Hasil penelitian menunjukkan nilai rata-rata Aiken's V sebesar 0,846, sebanyak 34 dari 35 butir (97,14%) memenuhi validitas empiris, reliabilitas sebesar 0,929, serta karakteristik butir didominasi tingkat kesukaran sedang, daya beda sangat baik, dan distraktor yang seluruhnya berfungsi efektif. Penelitian ini berkontribusi menyediakan instrumen HOTS yang valid, reliabel, serta model pengembangan instrumen berbasis evaluasi psikometrik untuk mendukung evidence-based formative assessment pada pembelajaran Akidah Akhlak.